Harvey Levenstein: Fear of Food. A History of Why We Worry about What We Eat - Jaine, Tom (Petits Propos Culinaires, 2012)
Harvey Levenstein: Fear of Food. A History of Why We Worry about What We Eat: University of Chicago Press, 2012, 218 pp., hardback, £18.95.